Nivolumab monotherapy in metastatic urothelial cancer (mUC): updated efficacy by subgroups and safety results from the CheckMate 032 study - Rosenberg, Jonathan E.; Jäger, Dirk (Annals of oncology, 2016)
© The Author 2016. Published by Oxford University Press on behalf of the European Society for Medical Oncology. All rights reserved. For permissions, please email: journals.permissionsoup.com.Background: Nivolumab has shown promising efficacy and acceptable safety in an open-label, multicenter phase I/II study in patients (pts) with mUC after ≥1 prior platinum-based therapy (NCT01928394). Here we report updated efficacy and safety results for the overall population based on additional follow-up and outcomes by differing levels of PD-L1 expression.Methods: Pts with mUC, unselected by PD-L1 expression status, received nivolumab 3 mg/kg IV every 2 wk until progression or discontinuation. Pts who met protocol criteria could continue treatment beyond progression and cross over to nivolumab + ipilimumab. Tumor PD-L1 membrane expression was assessed with Dako PD-L1 immunohistochemical staining. Primary endpoint: objective response rate (ORR; RECIST 1.1); other endpoints: safety, progression-free survival (PFS), overall survival (OS), and duration of response.Results: Of 78...